Modeling, validation and firing-on-the-move control of armored vehicles using active front-wheel steering. (April 2016) - Abd Kadir, Zulkiffli; Hudha, Khisbullah; Zamzuri, Hairi; Mazlan, Saiful Amri; Murrad, Muhamad; Imaduddin, Fitrian
It is a well-known fact that an armored vehicle will lose its directional stability when firing a large-caliber gun while moving. The instability is caused by the impulse force from firing, acting at the center of a weapons platform that produces a yaw moment at the center of gravity of the armored vehicle. In order to improve the stability, this paper introduces a firing-on-the-move technology for armored vehicles using an active front-wheel steering (AFS) system. The AFS system is proposed to maintain the directional stability of the armored vehicle by providing an electronically controlled correction to the steering mechanism. The steering correction is designed to reject the unwanted yaw motion and bring the vehicle back to its intended direction of travel after firing. The proposed control strategy of the AFS system in this study consists of yaw rate feedback with lateral force rejection control. The AFS system controller is developed on a validated 10-degrees-of-freedom armored vehicle. The results indicate that the developed control strategy can effectively maintain the directional stability, in terms of yaw and lateral motions, of the armored vehicle after firing. The superiority of the proposed AFS system controller is also evaluated by comparing its performance to an AFS system without lateral force rejection control as well as to a conventional armored vehicle without AFS.